A Ba‐free sealing glass with a high coefficient of thermal expansion and excellent interface stability optimized for SOFC/SOEC stack applications. Issue 4 (6th February 2018) - Ritucci, Ilaria; Agersted, Karsten; Zielke, Philipp; Wulff, Anders Christian; Khajavi, Peyman; Smeacetto, Federico; Sabato, Antonio Gianfranco; Kiebach, Ragnar
Abstract: A new glass‐ceramic composition containing Si, Mg, Ca, Na, Al, Zr, and B is presented here as sealant for planar SOFCs/SOECs, with the aim of joining the metallic interconnect (Crofer22APU) to the solid oxide cell (YSZ electrolyte or CGO barrier layer). Characteristic temperature, thermo‐mechanical properties, and compositional variations are reviewed and discussed by thermal analyses and in situ XRD, in order to design and optimize the sealing profile and reduce the residual porosity. The glass after heat treatment partially devitrifies into augite and nepheline with residual glass phase of around 64.3%; after crystallization the glass‐ceramic sealant has a coefficient of thermal expansion of 12.8 × 10 −6 K −1 and it is compliant with the other materials typically used for stack components. This work shows that the developed glass‐ceramic can successfully join the ceramic cell with the Crofer22APU (preoxidized and alumina coating), proven by tests on small and large‐scale samples. No signs of unwanted reactions at the glass‐metal and the glass‐cell interface are observed and sufficient gas tightness is achieved.